2019
DOI: 10.1101/753962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Developmental Transcriptome ofAe. albopictus,a Major Worldwide Human Disease Vector

Abstract: Aedes albopictus mosquitoes are important vectors for a number of human pathogens including the Zika, dengue, and chikungunya viruses. Capable of displacing Aedes aegypti populations, it adapts to cooler environments which increases its geographical range and transmission potential. There are limited control strategies for Aedes albopictus mosquitoes which is likely attributed to the lack of comprehensive biological studies on this emerging vector. To fill this void, here using RNAseq we characterized Aedes al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 92 publications
2
4
0
Order By: Relevance
“…Pairwise correlation analysis revealed that almost every developmental stage is most highly correlated with its adjacent stage and is very similar to what was previously found (Additional file 1: Fig. S6) [63]. To visualize the various patterns of gene expression and the relationships between the samples, hierarchical clustering and principal component analyses were performed (Additional file 1: Fig.…”
Section: Developmental Transcriptional Profilesupporting
confidence: 77%
See 3 more Smart Citations
“…Pairwise correlation analysis revealed that almost every developmental stage is most highly correlated with its adjacent stage and is very similar to what was previously found (Additional file 1: Fig. S6) [63]. To visualize the various patterns of gene expression and the relationships between the samples, hierarchical clustering and principal component analyses were performed (Additional file 1: Fig.…”
Section: Developmental Transcriptional Profilesupporting
confidence: 77%
“…The analyses of gene expression profiles across all developmental time points showed that the number of expressed genes (transcripts per million ≥ 1) gradually increases through embryogenesis, reaching its highest peak at 68-72 h (Additional file 10). As previously observed, there is an increase in the number of expressed genes during the early pupal stages, and the male germline expresses the highest number of genes among all samples [63]. After a blood meal, female mosquitoes undergo a series of physiological changes to support oogenesis.…”
Section: Developmental Transcriptional Profilesupporting
confidence: 51%
See 2 more Smart Citations
“…The RNA integrity was assessed using an RNA 6000 Pico Kit for Bioanalyzer (Agilent Technologies #5067-1513). The RNA-seq libraries were constructed using NEBNext Ultra II RNA Library Prep Kit for Illumina (NEB #E7770) following the manufacturer's instructions [51]. The libraries were sequenced on an Illumina HiSeq2500 in single read mode with a read length of 50 nt and a sequencing depth of 20 million reads per library following the manufacturer's instructions.…”
Section: Illumina Rna-sequencingmentioning
confidence: 99%